FLUKTUASI HARGA DAN ALUR DISTRIBUSI IKAN LAYANG (Decapterus spp) DARI HASIL TANGKAPAN MINI PURSE SEINE YANG DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA PEKALONGAN - Nugroho, Bramasto Ari; Boesono, Herry; Bambang, Azis Nur (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Fishery resources is a biological resources which have potency and enable to famous be received as wide and deeply. In effort to keeping fishery resources to be advance we need the widely knowledge about it. Therefore, in the present time we should be save the sea resourcesin a particular fishery resources for our generation in the future life. In this final project the research was taken in the Harbour of Pekalongan Nusantara Fishery Office. And TPI Pekalongan Nusantara Fishery Harbour Which have high level in operational and total fishery production income is so high enough and can hold many fishery ship. TPI PPN in Pekalongan is also as a corporation in fish marketing or distributing and the fuction to fish auction after the gain of fish cost. This research aims were to know the factors that affect the price of mackeel, to know the channel distribution, and analyze factor that had influence to the price fluctuation of mackerel fish. This research used a descriptive explorative data method using with quesionnaire to fisherman, fish sellers, and employers in Pekalongan Nusantara Fishery Port. The Primer Data got from an interview to the respondent directly, and Secondary Data got from Nusantara Fishery Port Office Pekalongan and the acknowlege that got from the instation which have connected with the object for research. Analysis data method with Double Linier regretion analysis with production function from Cobb doudlas and Double with helping program corelation analization with SPSS 17. This research can be factor that significantly attected in cost fluctuation was total production, if total mackerel fish production so much the cost of it is cheap and stable, if macarel fish production just a little so it would be expensive and not stable. The distribution channel in Pekalongan Nusantara Fishery Port is a distribution channel with direct and indirect.